Asah skill: An approach skill-based learning platform with management and strategic planning process - Ellin Devihana Pratiwi; Hendrik Amrico; Muhammad Afiff Rizki; Resti Savira; Catur Apriono (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2022)
Digital transformation in education improves entities by implementing significant changes in education by combining information technology, computing, communication, and coordination. This paper proposes improving education through a digital transformation through platforms, specifically online skills-based learning called ASAH Skill. The survey was conducted by collecting question data from Google Forms. By using the Problem Validation method and Primary Data, obtained Product Validation on Customer Needs (Survey) and Product Strategy (Affinity Diagram). It is a market-based validation as a guide for designing ASAH Skill products that meet the criteria and needs of Skill Providers and Seekers. The method considered consists of three steps, namely strategic situation analysis (SSA), strategy formulation (SF), and strategy implementation (SI). We have finally found what customers need to develop their skills during the isolation period of the covid-19 pandemic. The survey was conducted on 51 respondents. Strategic Implementation consists of Mockup, Business Model Canvas (BMC), and Problem Solution Fit Canvas. The biggest detention experienced by respondents was very limited mobility (82.4%). The survey also showed that most of the activities respondents did during the pandemic were exploring new things (37.3%). Video editing is the most learned skill during the pandemic (25.9%), and YouTube is the respondents' main choice as a medium for learning skills (43.1%). Overall, the results of the study show that dispensing and learning skills are a new need for society during a pandemic. The provision of a platform is a development opportunity as a forum for the dissemination and learning of skills. The highest priority is on the 'easy to use' attribute where all respondents give an importance rating of 5.